Evolution of information communication technology / Nor Amirah Mohd Norroe and Nurul Adelina Zainudin - Mohd Norroe, Nor Amirah; Zainudin, Nurul Adelina (Faculty of Information Management, 2015)
Information Communication of Technology (ICT) refers to technologies that provide access to information through telecommunication. Telecommunication is the transmission of information through sounds, words or visuals from a distance such as radio, television, phone, computer and network hardware and software. In the past few decades, information and communication technologies have provided society with a vast array of new communication capabilities. This article discuss about the old and new communication technology. People can choose which technology they want to use and follow. Anywhere we can go, we can see the different of an invention. Fact, they come in variety of form and style. Besides that, it also include about effect in evolution of information communication technology towards environment and humanity. After the development of communication technology there have an effect in every sort of field such as our society, transportation, communication, construction and education.